Knowledge on Antibiotic Use, Self-Reported Adherence to Antibiotic Intake, and Knowledge on Multi-Drug Resistant Pathogens – Results of a Population-Based Survey in Lower Saxony, Germany - Raupach-Rosin, Heike; Rübsamen, Nicole; Schütte, Gesa; Raschpichler, Gabriele; Chaw, Pa Saidou; Mikolajczyk, Rafael (Frontiers in Microbiology, 2019)
Introduction Assessment of public awareness on antibiotic use and resistance can identify key issues for campaigns addressing these problems. Our aim was to assess the knowledge, attitudes, and practice (KAP) related to antibiotic use and multi-drug resistant (MDR) pathogens in a general population in Germany. Methods We conducted a KAP survey on antibiotics and on MDR pathogens using an online panel recruited from the general population, which was established using stratified random sampling from the population registry in four districts in Lower Saxony, Germany. Results In the 12 months preceding the survey, 32.3% of the participants had received at least one prescription for antibiotics, 95.7% reported to follow the recommendations of prescribers, and 10.3% reported to stop taking antibiotics as soon as they feel better. Up to 94.9% of the participants had heard of MDR pathogens, 42.7% reported to know somebody who had been tested positive for it, 0.8% had an infection with it, and 37.2% were worried of contracting it. In case of contact with a carrier of MDR pathogens, over 90% would increase hand hygiene and 0.8% would avoid the carrier completely. Participants considered health care workers (75.1%) and everybody in society (87.8%) to be responsible for combating the spread of MDR pathogens. Conclusion There is a high reported exposure to antibiotics and awareness of the problem of MDR pathogens. Despite personal worries, most of the participants indicated a reasonable, non-stigmatizing behavior toward carriers of MDR pathogens, and that every individual was responsible to avoid their spread.